Lexicographical Problems in isiXhosa - Mini, Buyiswa M. (Lexikos, 1995)
Working on the lexicography of isiXhosa has led to the interesting experience of discovering that the description of the lexicon of isiXhosa poses innumerable challenges of both a semantic and a non-semantic nature. The problems encountered, some of which this article is an account of, include lack of understanding of the nature, depth and volume of work involved in compiling dictionaries, complexities idiosyncratic to the language itself, factors affecting consistency in methodology and other aspects, as well as extra-linguistic issues like orthography, finance, technology and relevant skills. Some of the problems rise from the very recognition of the fact that dictionaries play a significant role in "... eliminating obstacles in communication" (Alberts 1992: 1) and the consequent desire or ambition to produce as perfect a dictionary as possible. Keywords: isixhosa, trilingual dictionary, multi-volume dictionary, cultural context, addenda, inclusion, authenticity, accuracy, language change, self created terms, indeterminacy, alphabetization, naturality, orthography, computer lexicography, research, language representativeness, language planning